Smart Trolley / Muhamad Syahmi Mat Suud - Mat Suud, Muhamad Syahmi; Mashasan, Muhammad Mustaqeem; Mamat Ayob, Muhammad Zulhilmi; AB Malik, Mohamad Isa; Ahmad, Nurhelmi Hashimi (2022)
With the help of modern technology, society has embraced the act of consumerism more than ever either through means of online shopping or physical shopping. Most of the consumers prefer physical shopping more than using the internet to buy their desired items as they can evaluate the quality and condition of the product. Shopping physically can be construed as going to a store or shop to buy desired items face-to-face. Technology that we have developed, EZCart, is a smart trolley cart that aims to assist and improve shoppers experience by significantly decreasing the time spent shopping. EZCart allows consumers to directly scan products at the cart and view their expenses using built-in screen above the handle of the cart. The pipeline for building the smart trolley cart is detailed in this paper, and a SWOT analysis is used to determine the product's strengths, weaknesses, opportunities, and threats. A survey has been distributed to a specific target market in order to collect information directly from consumers about their preferences, habits, and experiences while shopping in any form. Furthermore, numerous prototype sketches are displayed, along with a full description of the design material used for the product. Under test marketing, shoppers were questioned if the product satisfied them and what their thoughts were about the product. Based on the responses gathered. Based on the responses gathered through the surveys, we can conclude that the respondents agree and can relate to the problem of long queuing and believe that EZCart can solve the problem effectively.